Bird's eyes view of Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2010)
This postcard provides an aerial view of the city of Port of Spain circa the early 1900s, showing scant occupation. In the distance the Port of Spain harbour can be seen. This used postcard dated 22nd July 1912, is addressed to someone in the United States of America, affixed are two Trinidad postage stamps.
Colour: Sepia (print); Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Trinidad and Tobago--Aerial Views; Cities and towns--Trinidad and Tobago--Port of Spain; Harbors--Trinidad and Tobago; 1912